Training operations reengineering survey - Shandler, Donald (Crisp Pub. Menlo ParkUS, 1997)
This survey instrument seeks to help trainers to evaluate and reengineer their organization's training function. Identifies 11 operational areas of the training function including: delivering technology-based training; designing learner-centered training; and, developing teams.